The moral dimensions of human rights - Wellman, Carl (Oxford University Press, 2011)
An approach to human rights -- The nature of moral human rights -- Gounds of moral human rights -- Moral dimensions of human rights documents -- The nature of international human rights -- Grounds of international human rights -- International rights versus national sovereignty -- Constitutional rights -- Judicial recognition of human rights -- Legislative recognition and implementation -- Recotgnition and implementation of treaty rights -- Moral dimensions